2000
DOI: 10.1121/1.1323233
|View full text |Cite
|
Sign up to set email alerts
|

Children’s perception of speech in multitalker babble

Abstract: Children 5, 9, and 11 years of age and young adults attempted to identify the final word of sentences recorded by a female speaker. The sentences were presented in two levels of multitalker babble, and participants responded by selecting one of four pictures. In a low-noise condition, the signal-to-noise ratio (SNR) was adjusted for each age group to yield 85% correct performance. In a high-noise condition, the SNR was set 7 dB lower than the low-noise condition. Although children required more favorable SNRs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
105
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 34 publications
10
105
0
6
Order By: Relevance
“…These findings concur with other research suggesting that children are less adept than adults at comprehending speech in ideal (Hazan & Barrett, 2000;Ohde & Haley, PRESCHOOL ACCENT COMPREHENSION 1997) and non-ideal listening conditions (Fallon et al, 2000(Fallon et al, , 2002. Findings of non-adultlike accent comprehension in young children are also consistent with accounts of protracted perceptual development (e.g.…”
supporting
confidence: 82%
“…These findings concur with other research suggesting that children are less adept than adults at comprehending speech in ideal (Hazan & Barrett, 2000;Ohde & Haley, PRESCHOOL ACCENT COMPREHENSION 1997) and non-ideal listening conditions (Fallon et al, 2000(Fallon et al, , 2002. Findings of non-adultlike accent comprehension in young children are also consistent with accounts of protracted perceptual development (e.g.…”
supporting
confidence: 82%
“…Vários testes clínicos foram elaborados para a avaliação da percepção da fala em crianças pequenas devido à necessidade de se estudar quais são as habilidades auditivas que a criança desenvolve frente ao uso dos aparelhos de amplificação sonora individuais (AASI) ou do implante coclear (IC) (2,3,4). Esses procedimentos permitem também avaliar o programa de habilitação ou reabilitação auditiva.…”
Section: Introductionunclassified
“…Numerous studies have shown differences between children and adults on a variety of speech-perception tasks in noise and reverberation (e.g., Fallon, Trehub, & Schneider, 2000;Hall, Grose, Buss, & Dev, 2002;C. E. Johnson, 2000) and in the presence of reduced spectral cues (Eisenberg, Shannon, Martinez, Wygonski, & Boothroyd, 2000).…”
Section: University Of Nebraska Lincoln Nebraskamentioning
confidence: 99%
“…Explanations include peripheral factors such as auditory sensitivity (Schneider, Trehub, Morrongiello, & Thorpe, 1986, central auditory processes (Allen & Wightman, 1994, attention and memory (Buss, Hall, Grose, & Dev, 1999;Hill, Hartley, Glasberg, Moore, & Moore, 2004;Wightman, Callahan, Lutfi, Kistler, & Oh, 2003), language experience (Eisenberg et al, 2000), poor information extraction (Grose, Hall, & Dev, 1997), and task difficulty (Fallon et al, 2000).…”
Section: University Of Nebraska Lincoln Nebraskamentioning
confidence: 99%